Worker Trainers as Workplace Experts: How Worker Trainers Enhance Safety and Health at Department of Energy Facilities. (March 2021) - Morawetz, John S.; Frazee, Tom; Ruttenberg, Ruth
Worker trainers not only teach health and safety in the classroom setting but also serve informally as important peer resources on the shop floor. They are often the "go to" people, for both hourly workers and managers, when there is a health or safety question—be it about tank vapors or personal protective equipment, confined space, or specific chemicals. These worker trainers actively use health and safety resource materials, both hard copy and online. Documented here, through two surveys of worker trainers—at U.S. Department of Energy facilities, trained through the International Chemical Workers Union Council Consortium of the Worker Training Program of the National Institute of Environmental Health Sciences—is documentation of this additional contribution that worker trainers make toward safer and more healthful work places.